Eficiência energética com enfoque agroecológico em agroecossistemas do semiárido brasileiro - Matias, Polyana da Costa (2017)
The objective of this article was to present the construction of a database formed by factor conversion tables to calculate net primary productivity and gross energy generated in agroecosystems of the Semiarid Region of Brazil; to evaluate the use of conversion factors tables for biomass and energy accounting in agroecosystems of the semiarid region of Ceará and; to carry out a comparative study of two agroecosystems through internal, external, final and agroecological Return on Energy (EROIs), dimensioning sustainability through energy efficiency parameters. The elaboration and utilities of the database containing factor conversion tables for biomass and energy of products commonly cultivated in the semi-arid region, based on regional and international bibliography, are presented. It was verified the need for more research on semiarid environment conditions and a deficiency of studies on organic and agroecological management systems was perceived. The factor conversion tables are not a static tool and should be broadened as well as improved their information quality. The use of the database for the calculation of biomass partitions in agroecosystems allowed bringing to light the complex biomass and energy flows in the studied agroecosystems. EROIs allowed quantifying the productive welfare of agroecosystems. The organic field proved to be efficient as a supplier of energy to society through the final and external EROIS. The mandala was more sustainable in the long term, due to its greater biodiversity and concern for the reinvestment of energy for the maintenance of agroecosystem sustainability funds. This was possible to be perceived through the internal EROIs, agroecological and the EROI final / EROI agroecological relationship. In this way, the agroecological EROI is an efficient parameter of sustainability. The study of EROIs allowed to reveal characteristics that were not evident in the agroeconomic analyzes carried out previously in these same agroecosystems, as is the case for the value for the final EROI parameter to be below the unit, suggesting the need to seek greater efficiency. The results show tradeoffs between different agroecosystem attributes and encourage multidimensional and interdisciplinary studies, incorporating economic, agronomic, ecological, social and political variables.